Six new recombinant inbred populations for the study of quantitative traits in Arabidopsis thaliana - O’Neill, Carmel M. (Springer-Verlag, 2008)
Quantitative approaches are now widely used to study the genetic architecture of complex traits. However, most studies have been conducted in single mapping populations, which sample only a fraction of the natural allelic variation available within a gene pool and can identify only a subset of the loci controlling the traits. To enable the progress towards an understanding of the global genetic architecture of a broad range of complex traits, we have developed and characterised six new Arabidopsis thaliana recombinant inbred populations. To evaluate the utility of these populations for integrating analyses from multiple populations, we identified quantitative trait loci (QTL) controlling flowering time in vernalized plants growing in 16 h days. We used the physical positions of markers to align the linkage maps of our populations with those of six existing populations. We identified seven QTL in genomic locations coinciding with those identified in previous studies and in addition a further eight QTL were identified. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00122-007-0696-9) contains supplementary material, which is available to authorized users.